1971
DOI: 10.1021/ba-1971-0100.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of Group IA and IIA Cations

Abstract: The biological function of Group IA and IIA cations of the periodic table is reviewed against the background of their chemistry. Utilization of these cations arises from an ability to form different types of complex compounds, which is dependent upon the radius-ratio effect. If the details of their biochemistry are to be understood, new probe methods for following the cations in biological systems must be devised. Some possibilities based upon the principle of isomorphous replacement are described and tested.*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The order (1) is found to coincide roughly with the order (2), although there is some alteration in the order of the alkali metal cations. As to the minor difference in the order of the ionic series, Williams (1971) suggested that the alteration is likely to occur when these cations interact with weak acid anions of biological ligands such as , Op4 -C02and -C032groups. It is, therefore, conceivable that the water response is easily affected by strength of the interaction between the previously adsorbed cation and some biological ligands such as phospholipids in the receptor membrane of the olfactory cell.…”
Section: Discussionmentioning
confidence: 99%
“…The order (1) is found to coincide roughly with the order (2), although there is some alteration in the order of the alkali metal cations. As to the minor difference in the order of the ionic series, Williams (1971) suggested that the alteration is likely to occur when these cations interact with weak acid anions of biological ligands such as , Op4 -C02and -C032groups. It is, therefore, conceivable that the water response is easily affected by strength of the interaction between the previously adsorbed cation and some biological ligands such as phospholipids in the receptor membrane of the olfactory cell.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were carried out at room temperature with freshly prepared solution. Magnetic susceptibilities were measured by Gouy method at room temperature using Hg[Co(SCN) 4 ] as a standard [32], and the magnetic moments were thus calculated. The cations and anions were estimated by using analytical procedure [33].…”
Section: Instrumentationmentioning
confidence: 99%
“…Many studies stressed the role of metal ions in biological processes, whereas the inorganic pharmacology started to be an important field, and more than 25 inorganic compounds have been pursued and are being used in various therapies as antibacterial, antiviral and anticancer drugs [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This pos sibility may operate specially in complexes of large molecules (macromolecules) which are able to generate steric fitting to accomodate to the cation size. Under these circunstances, the radius-ratio effect is not so important as in the case of multi chelating agents of rigid structure [16] and consequently the nature of the cation charge could play a more important role. On the other hand, the accumulation of radiolanthanides by tumors [17] can be interpretated in a similar way than 67Ga uptake by a process of ionic replacement [6], The present experimental results and previous observations of a higher 67Ga accumulation in tissues such as liver, spleen, stomach and kidney, which show a high magnesium or calcium content [6] appear to corroborate the hypothesis of 67Ga competition for Ca2+ and Mg2+ binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the accumulation of radiolanthanides by tumors [17] can be interpretated in a similar way than 67Ga uptake by a process of ionic replacement [6], The present experimental results and previous observations of a higher 67Ga accumulation in tissues such as liver, spleen, stomach and kidney, which show a high magnesium or calcium content [6] appear to corroborate the hypothesis of 67Ga competition for Ca2+ and Mg2+ binding sites. That most of those binding sites are located in macromolecular structures has been already demonstrated [6,16,18], and among them macromolecular binders such as lipo-and nucleoproteins are well known to be associated with magnesium and calcium in mammalian tissues [19], Furthermore, tumor cells accumulate considerable amounts of both Ca2+ and Mg2+ [18,21] which are two elements playing a key role in the control of cell proliferation and growth [22-25«. At this respect it should be mentioned that a correlation between cellular incorporation of 67Ga and rate of cellular proliferation has been observed »26], Our own observations indicate that the concentration of magnesium in experimental tumors increases during the period of higher growth rate [18].…”
Section: Discussionmentioning
confidence: 99%